The Health and Safety Perspectives in the Zimbabwe Public Sector - Mapuvire, Davidzo H.; Chilunjika, Sharon R. T.; Mutasa, Florence (Springer, Singapore, 2022)
This chapter is a review of the occupational health and safety measures in the public sector to determine their adequacy in ensuring the wellbeing of the employees in the working environment. The goal of occupational health and safety measures is to prevent or at least minimize the chances of injuries, deaths and diseases arising from the working environment. Like many other countries, Zimbabwe is a signatory to the International Labour Organisation (ILO) Conventions on occupational health and safety. The country has developed policy, legislation and institutional frameworks on occupational health and safety at sectoral, organisational and national levels. The study adopted an exploratory qualitative design and data was gathered through the desktop to determine any gaps in terms of occupational health and safety strategies in place. The study results established that the occupational health and safety measures in the public sector are inadequate. The country lacks a comprehensive and harmonized occupational health and safety legal framework. The study recommends that the government of Zimbabwe should take adequate preventative and protective measures to ensure a safe working environment for all workers in the public sector.